The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/14649365.2021.2000019
|View full text |Cite
|
Sign up to set email alerts
|

‘We may be long in the tooth, but it makes us tough’: exploring stillness for older adults during the COVID-19 lockdowns

Abstract: Following the outbreak of the SARS-CoV-2 across the world in 2020, millions of people were reduced in their mobility to hinder the spread of the disease. The lockdown was particularly difficult for older adults, who were deemed 'vulnerable' because many felt unsafe leaving the house and often forced to self-isolate. In this paper, we interpret the lockdowns as a period of prolonged stillness: breaks from everyday practices, including withdrawnness, inefficiency, and retreat. We extend ideas of stillness by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…It was, however, not only the spaces for children and youngsters but also those where grown-ups and the elderly used to meet that were suddenly missing. Like Smith et al (2020) and Osborne and Meijering (2021) point out, many elderlies felt unsafe about leaving home and were forced to isolate themselves during the lockdowns. When community centres and sports centres closed, residents and social workers in the areas could clearly feel the importance of such local spaces in facilitating their everyday social interaction.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was, however, not only the spaces for children and youngsters but also those where grown-ups and the elderly used to meet that were suddenly missing. Like Smith et al (2020) and Osborne and Meijering (2021) point out, many elderlies felt unsafe about leaving home and were forced to isolate themselves during the lockdowns. When community centres and sports centres closed, residents and social workers in the areas could clearly feel the importance of such local spaces in facilitating their everyday social interaction.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Studies conclude that the media's representation and a high amount of negative media coverage increase stigma in these vulnerable areas and negatively affect the residents (Arthurson, 2013;Jensen & Christensen, 2012;. Another group particularly vulnerable during the pandemic were the elderly, and some studies show that a large group of elderly were unsafe about leaving home and often forced to isolate themselves (Osborne & Meijering, 2021;Smith et al, 2020). The pandemic emphasised the need for local organizations and volunteers to provide services and help the elderly during these periods of isolation and increased risk of loneliness (Smith et al, 2020, p. 1).…”
Section: State Of the Art: Social Infrastructure Disadvantaged Neighb...mentioning
confidence: 99%
“…In fact, sharing household responsibilities by elderly parents of the extended family is quite prevalent in Asian countries in the pre-pandemic period (Chui, 2007), but its changes during the COVID-19 lockdown have been given little attention. Existing literature in the Western context frequently depicts the elderly as vulnerable groups and describes the challenges and difficulties they face during the COVID-19 lockdown (Buffel et al, 2021; Osborne and Meijering, 2021), but it has largely ignored how those in extended families interact with their adult children. It is possible that when the elderly are in poor health or at high health risk during a pandemic, adult children would face more responsibilities for looking after them.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Much of this work has examined the sharp sociospatial inequalities accompanying the pandemic, and efforts to respond to them (Lutpon & Willis, 2021). There have been calls for greater attention to vulnerability and death (Shchglovitova & Pitas, 2022), including differential vulnerabilities amongst elderly groups (Osborne & Meijering, 2021) or people with learning disabilities (Macpherson et al, 2021; Van Holstein et al, 2023), and research on how the pandemic intersects with social geographies of health, mobility, housing, employment, care, prisons and the arts (Ho & Maddrell, 2021; McEwan et al, 2022; Schliehe et al, 2022). To take one example, in a rich account of how garment workers experienced the pandemic in Cambodia, Brickell et al (2022) revealed the social knock‐on effects of restrictions as workers received reduced wages which led to them eating less, struggling to pay back debt, and becoming increasingly worn out.…”
Section: Introductionmentioning
confidence: 99%